Mutation of the NOP10 gene as a cause of steroid-resistant nephrotic syndrome coexisting with cataract, hearing loss, and enterocolitis - Ogarek, Iwona; Szczęsny-Choruz, Elżbieta; Drożdż, Dorota (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Nephrotic syndrome comprises a set of symptoms caused by proteinuria exceeding the compensatory capabilities of the body. Based on treatment response, it is classified as either steroid-sensitive or steroid-resistant nephrotic syndrome (SRNS). Steroid resistance is an indication for kidney biopsy and genetic testing. In our case, SRNS in a 6-year-old boy was accompanied by bilateral cataracts, sensorineural hearing loss, and enterocolitis. Genetic testing revealed a previously unreported homozygous mutation in the NOP10 gene. The nucleolar protein NOP10 belongs to a family of ribonucleoproteins that play a crucial role in maintaining proper telomere function and RNA maturation through pseudouridylation. Limited literature reports describe a family with a phenotype similar to that of our patient, in which NOP10 gene mutations led to reduced pseudouridylation and ribosome dysfunction. Considering these findings, it seems likely that defective pseudouridylation represents a novel pathogenic mechanism linking kidney, eye, ear, and intestinal abnormalities in our case.